2019
DOI: 10.1038/s41598-019-39082-9
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract promotes DNA repair in a yeast model

Abstract: Green tea polyphenols may protect cells from UV damage through antioxidant activities and by stimulating the removal of damaged or cross-linked DNA. Recently, DNA repair pathways have been predicted as possible targets of epigallocatechin gallate (EGCG)-initiated signaling. However, whether and how green tea polyphenols can promote nucleotide excision repair and homologous recombination in diverse organisms requires further investigation. In this report, we used the budding yeast, Saccharomyces cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
(46 reference statements)
0
7
0
2
Order By: Relevance
“…GTex reduces the genotoxic effects by reducing free radicals and protecting thiol groups and also has a positive effect on the DNA repair mechanism. Chong et al ( 2019 ) reported that GTex enhances expression of DNA repair genes in yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…GTex reduces the genotoxic effects by reducing free radicals and protecting thiol groups and also has a positive effect on the DNA repair mechanism. Chong et al ( 2019 ) reported that GTex enhances expression of DNA repair genes in yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies across humans, animals and cell models provide evidence that polyphenols may increase the activity and expression of endogenous antioxidant enzymes, and reduce both markers of oxidative DNA damage and occurrence of strand breaks (often in response to DNA-damaging agents) [ 54 , 55 ]. Polyphenols have further been shown to increase the expression of DNA damage repair genes in yeast [ 56 ] and mice [ 57 ] under UV challenge. These studies suggest that polyphenols are biologically active when consumed, however the exact mechanism by which they may limit DNA damage in spermatozoa is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Since the issue of the dry hopping beer's quality is considered, it is necessary to consider favorable conditions for the extraction of hop polyphenol complex compounds in the presence of polar solvent (ethanol) and yeast cells, taking into account the metabolic transformations of different polyphenols [45][46][47][48], the data are presented in Table 3.…”
Section: The Determination and Mathimatical Analysis Of The Beer's Phenolic Compounds Compositionmentioning
confidence: 99%